Desain Pembelajaran Daring Statistika Berbasis Higher Order Thinking Skills Untuk Siswa SMP - Rosselyne (Jurnal Riset Pendidikan Matematika Jakarta, 2022)
This article presents the development of instructional design in conditions of online learning following the Dick, Carey & Carey model on the topic of statistics for 7th grade of junior high school students in the 2nd semester. The material that will be discussed is presenting data. The instructional design was developed based on Higher Order Thinking Skills (HOTS), using Project-based Learning aided Microsoft Excel and Edmodo as a Learning Management System (LMS). The development begins with identifying and analyzing learning and students’ characteristics. Performance objectives, instrument assessment, development of learning strategies, formative and summative evaluation plans are also discussed in detail and in harmony with each other. At the end, we discuss things that must be considered in the implementation process.